2020
DOI: 10.1016/j.jmig.2019.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Transabdominal Cerclage vs Laparotomy: A Comparison of Obstetric and Surgical Outcomes

Abstract: To compare obstetric and surgical outcomes of transabdominal cerclage (TAC) via laparotomy (TAC-LAP) versus robotic-assisted (TAC-RA) approaches. Design: Retrospective cohort study. Setting: An academic medical center. Patients: Sixty-nine women with acquired or congenital cervical insufficiency. Interventions: All women underwent TAC either by laparotomy or robotic-assisted approaches by 2 primary surgeons between January 2003 and July 2018. Women with a preconceptional TAC without a subsequent pregnancy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…An open approach to TAC placement via laparotomy (TAC-lap) was first described in the 1960 s and a laparoscopic approach (TAC-lsc) was first used in the late 1990 s. Laparoscopy is generally preferred to laparotomy given improved visualization and lower rates of hemorrhage, wound complications, postoperative pain, length of hospital stay, and subsequent adhesive disease. Multiple studies have confirmed that TAC-lsc is associated with a statistically significant decrease in blood loss, wound infections, and length of hospital stay when compared to TAC-lap [17 ▪▪ ,21,22].…”
Section: Transabdominal Cerclagementioning
confidence: 95%
“…An open approach to TAC placement via laparotomy (TAC-lap) was first described in the 1960 s and a laparoscopic approach (TAC-lsc) was first used in the late 1990 s. Laparoscopy is generally preferred to laparotomy given improved visualization and lower rates of hemorrhage, wound complications, postoperative pain, length of hospital stay, and subsequent adhesive disease. Multiple studies have confirmed that TAC-lsc is associated with a statistically significant decrease in blood loss, wound infections, and length of hospital stay when compared to TAC-lap [17 ▪▪ ,21,22].…”
Section: Transabdominal Cerclagementioning
confidence: 95%
“…The laparoscopic approach is favored for many procedures given reduced blood loss, fewer wound complications, a shorter length of stay, and a faster return to normal activities compared with an open approach (28-30). These advantages likely apply to laparoscopic abdominal cerclage, and one study confirmed reduced blood loss and reduced length of stay with a robotic-assisted laparoscopic abdominal cerclage compared with an open abdominal cerclage (31). Laparoscopy lends improved visualization of the pelvic anatomy, aiding in avoidance of uterine vessel injury, a feared complication of abdominal cerclage.…”
Section: Laparoscopic Approachmentioning
confidence: 98%